The Militant Worker: Class and Radicalism in France and America. (English) - Bélanger, Paul R. (Labour / Le Travail, 1988)
This article reviews the book, "The Militant Worker: Class and Radicalism in France and America," by Scott Lash.
Keywords: LASH, Scott; MILITANT Worker: Class & Radicalism in France & America, The (Book); Nonfiction; REVIEWS; Radicalism; books